Ethanol extract of Dryopteris crassirhizoma alleviates allergic inflammation via inhibition of Th2 response and mast cell activation in a murine model of allergic rhinitis. (25th March 2019) - Piao, Chun Hua; Kim, Tae-Geum; Bui, Thi Tho; Song, Chang Ho; Shin, Dong Uk; Eom, Ji-Eun; Lee, So-young; Shin, Hee Soon; Chai, Ok Hee
Abstract: Ethnopharmacological relevance: Dryopteris crassirhizoma (DC) is used as a traditional herbal remedy to treat various diseases, the tapeworm infection, common cold, and cancer in Korea, Japan, and China. DC also has the antioxidant anti-inflammatory and antibacterial activities. However, the anti-allergic inflammatory effect of DC and some of its mechanisms in allergic rhinitis model are unknown well. Aim of this study: The purpose of this study is to investigate the anti-allergic inflammatory effect of DC on the allergic rhinitis model, mast cell activation and histamine release. Materials and methods: Allergic rhinitis was induced in BALB/c mice by sensitization and challenge with ovalbumin (OVA). Different concentration of DC and dexamethasone was administrated by oral gavage on 1 h before the OVA challenge. Mice of the control group were treated with saline only. Then mice were evaluated for the presence of nasal mucosa inflammation, the production of allergen-specific cytokine response and the histology of nasal mucosa. Results: DC significantly ameliorated the nasal symptoms and the inflammation of nasal mucosa. DC also reduced the infiltration of eosinophils and mast cells in these tissues and the release of histamine in blood. Meanwhile, DC evidently inhibited the overproduction of Th2 cytokines and increased the Th1 and Treg cytokines in nasal lavage fluid by OVA. DC also reduced the levels of OVA-specific IgE, IgG1 and IgG2a in blood. Conclusions: This study suggests that DC has a significant anti-allergic inflammatory effect in the nasal cavity. DC may have the therapeutic effect of allergic rhinitis. Graphical abstract: